Image classification using hybrid method - Ielaf O. abdl-majjed al dahl (College of Education for Pure Sciences, 2012)
Abstract This paper find a method depending on combining both classic and artificial methods to classify (recognition) an image.k-means method is used to find the main characteristics of the images. Then these images are classified using Hamming and Maxnet Artificial Neural Networks (ANNs). The proposed method is compared with the artificial one only. Three parameters are used for this comparison, number of iteration, second Peak Signal to Noise Ratio (PSNR) and third correlation. The results reveal that the used method is better than artificial method. correlation for proposed method is equal (0.5360), while it is (0.4610) for artificial method applying the same input JPEG image. This software is applied on JPEG and BMP gray images type. MATLAB 7.6.0 is utilized for the implementation of this software.